The Design of Local Wisdom-Based Science Learning on Pressure Materials in Junior High School - Aulia Eka Putra; Jufrida Jufrida; Haerul Pathoni; Fibrika Rahmat Basuki (Journal of Science Education Research, 2021)
The lesson plan is an important aspect that determines the success of learning in the classroom. Teachers must design learning that can relate the material being studied to the daily lives of students, for example, is through integrated local wisdom into science learning. The study aimed to develop a science learning set of local wisdom based on pressure materials in Junior High Schools. The research was research and development and used a 4D development model (Define, Design, Development, and Disseminate). The subjects were material experts, media experts, and science teachers of junior high school. The instrument was a validation sheet of the learning set. Qualitative data were analyzed descriptively, and quantitative data were analyzed using descriptive statistics. This research produces a science learning set of local wisdom-based on pressure materials in junior high schools, consisting of syllabus, lesson plans, assessments, student worksheets, teaching materials, remedial and enrichment programs. The results of expert validation obtained a score of 89.60 with an excellent category. The results of the science teacher assessment were 92.38 with excellent category. In sum, the science learning set of local wisdom based on pressure material in junior high schools was valid and feasible to improve the understanding of science concepts.